Consejo universitario. (UNED, 2024)
De izquierda a derecha José Antonio Blanco, Ramiro Porras, Fernándo Brenes Espinoza, María Eugenia Bozzoli Vargas, Don Rodrigo Arias Camacho, Marlen Víquez Salazar, Juan Carlos Parreaguirre Camacho y Carlos Morgán Marín